Usage and impact metrics for Parliamentary libraries. (June 2019) - Al Baghal, Tarek
Parliamentary libraries are important in supporting informed decision-making in democracies. Understanding Members' information needs is important, but the usage and impact of these libraries have been less explored. A particular example of the United Kingdom's House of Lords Library is studied, collecting and analysing data using techniques from the field of data science. These techniques are useful in extracting information from existing sources that may not have been designed for the purpose of data collection. A number of data sources available at the Lords Library are outlined and an example of how these data can be used to understand Library usage and impact is presented. Results suggest that Member usage varies significantly and that there is a small but significant relationship between usage and making speeches in the chamber. Further work should explore other indicators of impact, but these methods show promise in creating library metrics, particularly in Parliamentary settings.